An attempt to assess functionally minimal acetylcholinesterase activity necessary for survival of rats intoxicated with nerve agents - Bajgar, Jiri; Fusek, Josef; Kassa, Jiri; Jun, Daniel; Kuca, Kamil; Hajek, Petr (Chemico-biological interactions, 2008)
Acetylcholinesterase (AChE, EC 3.1.1.7) is an important enzyme for cholinergic nerve transmission. The action of toxic organophosphates such as nerve agents is based on AChE inhibition. The death following acute nerve agent poisoning is due to central or peripheral respiratory/cardiac failure. Therefore, the changes in AChE activity following nerve agents acting predominantly on the central (sarin, soman) or peripheral (VX) level were studied. It is known that AChE activity in different structures exists in relative excess. Female Wistar rats intoxicated with sarin, soman, and VX in different doses (0.5-2.0 x LD(50)) were divided into groups of survived and died animals. AChE activities in diaphragm, brain parts (pontomedullar area, frontal cortex, basal ganglia, in some cases other parts of the brain) were determined and the rest of activity (in %) was correlated with survival/death of animals. More precise elucidation of action of nerve agents and the assessment of minimal AChE activity in different organs compatible with the survival of organism poisoned with nerve agents were the aims of this study.
Keywords: LD50; acetylcholinesterasa; krysa rodu Rattus; Cholinesterase Inhibitors; chemické bojové látky; potkani Wistar; Lethal Dose 50; Chemical Warfare Agents; Animals; Rats, Wistar; Female; ženské pohlaví; Acetylcholinesterase; cholinesterasové inhibitory; zvířata; Rats